A mixed methods approach investigating cognitive changes in vicarious trauma within trainees and qualified therapists - Millard, Emma Louise (2017)
Background: Previous research has explored the impacts of empathically engaging with client trauma accounts on therapists. The majority of this has been quantitative, guided by measures of secondary traumatic stress symptoms or belief-disruptions consistent with Constructivist Self-Development Theory (CSDT). Results have been inconsistent and interpretation is affected by methodological shortcomings. There have also been differences in findings between qualitative and quantitative approaches. Whilst most quantitative measures focus on the negative impacts of trauma work, qualitative studies have revealed the presence of positive impacts; referred to as vicarious posttraumatic growth. A review of previous literature, addressing their methodological limitations, is presented.